A novel form of the membrane protein CD147 that contains an extra Ig-like domain and interacts homophilically - Hanna, S; Kirk, P; Holt, O; Puklavec, M; Brown, M; Barclay, A (2003)
Background: CD147 is a broadly distributed integral membrane glycoprotein with two Ig-like domains implicated in a wide range of functions. It is associated at the cell surface with the monocarboxylate transporters MCT1 and 4 but interactions of the extracellular region have not been characterised. Results: We report the characterisation of a form of CD147 with an additional membrane-distal Ig-like domain. In contrast to the two domain form, this three domain form of CD147 interacts homophilically. Surface plasmon resonance analysis using recombinant proteins showed that the interaction was of low affinity (KD ∼ 40 μM) and this is typical of many interactions between membrane proteins. cDNA for the 3 domain form are rare but have been identified in human and mouse retina. Conclusion: The finding that the three domain form of CD147 has an extracellular ligand, that is it interacts homophilically, suggests this interaction may be important in aligning lactate transporters in the retina where lactate is an important metabolite.